Further delineation of the Baller-Gerold syndrome - Lin, A E; McPherson, E; Nwokoro, N A; Clemens, M; Losken, H W; Mulvihill, J J (American journal of medical genetics, 1993)
Three new patients with the Baller-Gerold syndrome bring the number of reported cases to 20. In addition to craniosynostosis involving various sutures and preaxial reduction defects of variable severity, affected patients may have anal, urogenital, cardiac, central nervous system, and vertebral defects. Autosomal recessive inheritance is supported by the presence of affected sibs and parental consanguinity.